2021
DOI: 10.1083/jcb.202007146
|View full text |Cite
|
Sign up to set email alerts
|

Effector-mediated ERM activation locally inhibits RhoA activity to shape the apical cell domain

Abstract: Activated ezrin-radixin-moesin (ERM) proteins link the plasma membrane to the actin cytoskeleton to generate apical structures, including microvilli. Among many kinases implicated in ERM activation are the homologues LOK and SLK. CRISPR/Cas9 was used to knock out all ERM proteins or LOK/SLK in human cells. LOK/SLK knockout eliminates all ERM-activating phosphorylation. The apical domains of cells lacking LOK/SLK or ERMs are strikingly similar and selectively altered, with loss of microvilli and with junctional… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 67 publications
6
32
0
Order By: Relevance
“…In this study, we observed the expressions of ezrin, radixin, moesin, and PD-L1 in HeLa cells at both mRNA and protein levels, all of which are in line with the previous observations using HeLa cells [ 44 , 45 , 48 , 49 ]. In another human cervical cancer cell line, OMC4, all three ERM were detected at protein levels, but the relative expression levels of radixin and moesin were lower than that of ezrin [ 50 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we observed the expressions of ezrin, radixin, moesin, and PD-L1 in HeLa cells at both mRNA and protein levels, all of which are in line with the previous observations using HeLa cells [ 44 , 45 , 48 , 49 ]. In another human cervical cancer cell line, OMC4, all three ERM were detected at protein levels, but the relative expression levels of radixin and moesin were lower than that of ezrin [ 50 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we observed the expressions of ezrin, radixin, moesin, and PD-L1 in HeLa cells at both mRNA and protein levels, all of which are in line with the previous observations using HeLa cells [44,45,48,49]. In another human cervical cancer cell line,…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we first detected the higher expression levels of PD-L1 together with ezrin and radixin, while also detecting considerably lower levels and a deficit of moesin at the genetic and protein levels in JEG-3 cells, respectively. The results of these observations are in accordance with those of previous reports that demonstrated an abundance of ezrin and radixin, in contrast to a lack of moesin, at the protein level in JEG-3 cells [ 38 , 42 ]. Therefore, moesin was excluded from subsequent analysis.…”
Section: Discussionsupporting
confidence: 92%
“…The mRNA expression levels of ezrin, radixin, and PD-L1 were sufficient to allow gene expression analysis ( Figure 1 a–c). While the mRNA expression of moesin was detected at a higher level in primary human umbilical vein endothelial cells (HUVEC) and HeLa cells, a human uterine cervix cell line, both have been used as positive control cells, in which moesin is abundantly present [ 35 , 36 , 37 , 38 ], while moesin levels were considerably lower in JEG-3 cells ( Figure 1 d, Figure S1 ). Similarly, protein expression levels of PD-L1, in addition to ezrin and radixin, were detected in whole cell lysates of JEG-3 cells ( Figure 1 e).…”
Section: Resultsmentioning
confidence: 99%
“…S1, C to E). Comprehensive literature search further revealed that many of these identified pairs have been reported before (data S2), including the antagonistic interaction between Ste20-like serine/threonine protein kinase (SLK) and ROCK via suppressive phosphorylation of RhoA by SLK ( 19 21 ), the synergistic interaction between fibroblast growth factor receptor 1 (FGFR1)/insulin-like growth factor 1 receptor and MAPK via classical receptor signaling cascade ( 22 26 ), and the antagonistic interaction between Rho GTPase Activating Protein 29 (ARHGAP29) and ROCK ( 27 29 ) via regulators of guanosine triphosphatase activities. Identification of these interaction pairs with literature support indicates that our screen has sufficient power to find important and specific shRNA-drug interactions.…”
Section: Resultsmentioning
confidence: 89%